Analysis of Management Strategies and Religious Beliefs of Families with Five or More Children - Arini Rizqina; Iradewi Cahyati; Rizky Asrul Ramadhan; Heni Ani Nuraeni (STMIK Indonesia Banda Aceh, 2026)
Indonesia in the contemporary demographic landscape is increasingly dominated by the norm of small nuclear families, while large families with more than five children are often seen as marginalized and burdened with social stigma. The narrative of state policies through Family Planning programs and modern economic discourse places the extended family as an